Basic Symptoms of Infectious Diseases - Muratova, Gulsara Saidovna; Qarshiyeva, Dilovar Rustamovna (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the types of airborne infectious diseases, the spread of fluids (saliva droplets) from the respiratory tract of a sick person in the room (speaking, coughing), the spread of infectious diseases in the respiratory tract of other healthy people through this contaminated air. The main tasks of the medical service are the prevention of infectious diseases and the preparation of timely treatment measures.